As contas públicas do Estado do Rio de Janeiro face à legislação de responsabilidade fiscal e previdenciária: 2000 a 2007 - Araújo, Fernando Graça Klautau de (2008)
With the introduction of Plano Real and the subsequent currency stability in the mid 90’s, the seriousness of the fiscal situation of the sub-national unities became evident. On one side, there were difficulties in conducting the financial management through the absence of an inflationary process, which had previously enabled the indexation of the tax revenues, whereas the settlement and payment of current expenses were postponed. On the other side, the consolidated debt, mostly concerning bonds, was increasing due to restrictive monetary policy. This uncertain financial situation urged the accomplishment of the States fiscal adjustment, lead by the Federal Government, which established ultimate measures to attain this purpose, three acts can be highlighted: The Union States Debts Renegotiation Act, The Social Security Responsability Act and The Fiscal Responsability Act. The present work studies the management of Rio de Janeiro public state accounts from 2000 to 2007, aiming at verifying the existence of fiscal adjustment efforts and how these efforts have brought adequate results, evidencing the effectiveness of these three acts established by the Federal Government. Pursuant to this work, it can be concluded that, within the period of 2000 - 2006, there was no significant progress towards the improvement of public state accounts, and the primary budget surplus attained in the period was stimulated by the increase of unstable, extraordinary and limited incomes. The inherent risks to the excessive and rising dependency of the state finances to the above mentioned incomes were highlighted in view of the fact that theses incomes have been used for the payment of continuous public current expenses. The present work also concludes that, as of 2007, the kick-off to obtain a fiscal adjustment was given, taking into account the change in the primary budget surplus level, stressing the reduction of primary budget expenses and not the increase in extraordinary incomes.